2007
DOI: 10.5194/angeo-25-2579-2007
|View full text |Cite
|
Sign up to set email alerts
|

Dual HF radar study of the subauroral polarization stream

Abstract: Abstract. The dual HF radars comprising the Tasman International Geophysical Environment Radar (TIGER) system often observe localized high-velocity F-region plasma flows (≥1500 m/s) in the midnight sector (20:00–02:00 MLT) at magnetic latitudes as low as Λ=60° S. The flow channels exhibit large variability in the latitudinal extent and electric field strength, and are similar to the subauroral polarization stream or SAPS, a plasma convection feature thought to be related to the polarization electric field due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 23 publications
7
47
0
Order By: Relevance
“…This feature was first reported on the basis of indirect Millstone Hill observations by Foster et al (2005). Makarevich and Dyson (2007) showed that SAPS flows can exist in a dormant state for a long time, for at least two substorm cycles, and they can be intensified by the substorm processes, in agreement with Anderson et al (1993).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…This feature was first reported on the basis of indirect Millstone Hill observations by Foster et al (2005). Makarevich and Dyson (2007) showed that SAPS flows can exist in a dormant state for a long time, for at least two substorm cycles, and they can be intensified by the substorm processes, in agreement with Anderson et al (1993).…”
Section: Introductionsupporting
confidence: 62%
“…Koustov (sasha.koustov@usask.ca) at high magnetic latitudes of >65 • (Greenwald et al, 1995). Several recent publications have demonstrated that some of the SuperDARN radars can also be useful for studies of subauroral polarization streams (SAPS), which are fast flows at or equatorward of equatorial edge of the auroral oval (Parkinson et al, 2003(Parkinson et al, , 2005Koustov et al, 2006;Makarevich and Dyson, 2007). SAPS events have been identified and investigated for relatively low-disturbed magnetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The only difference is the existence of the polarization stream (FCP2) before SLE onset that could be associated with enhanced auroral activity before SLE. A similar event was presented in Makarevich and Dyson (2007).…”
Section: Peculiarity Of Signals Scattering In Ionospheric F2 Layermentioning
confidence: 62%
“…In five maps, the three separated flow channels are visible: two with V D > 0 (red symbols) and one with V D < 0 (blue symbols). Based on results of previous investigations (e.g., Makarevich andDyson 2007, Zou et al 2009 and references therein), we suppose that a western high-latitude flow channel of positive V D (FCP1) may be associated with eastward auroral jet , a flow channel of negative V D ( FCN), located to the east of FCP1 , is related to westward jet, and a low-latitude flow channel of positive V D (FCP2) is caused by the polarization stream.…”
Section: Peculiarity Of Signals Scattering In Ionospheric F2 Layermentioning
confidence: 99%
“…The beam-swinging technique (Makarevich and Dyson 2008) is applied for each bin to deduce a twodimensional flow vector. This method has originally been used by Ruohoniemi and Greenwald (1996) (see Figure 1 in their paper) to statistically deduce the average high-latitude convection map from SuperDARN LOSV observations.…”
Section: Methodsmentioning
confidence: 99%